Persepsi Siswa terhadap Pembelajaran Berbasis Proyek dalam mata pelajaran Kimia : Analisis Kualitatif di SMA RAMU Bogor - Abdurahman, Ayi; Setiawati; Erwini Christine, Sri; Pradesa, Kohar (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
This study explores the effectiveness of project-based learning (PBL) in enhancing students' understanding of chemistry concepts. Utilizing a qualitative approach and a case study design, data were collected through in-depth interviews, classroom observations, and document analysis, which were thematically analyzed. The results indicate that students have a positive perception of PBL, as evidenced by their active engagement in group discussions and experiments. PBL has been shown to improve the understanding of chemistry concepts, enabling students to explain and apply these concepts in real-world contexts. Three main themes identified are: (1) student engagement and motivation, (2) skills developed, and (3) barriers to the implementation of PBL. High levels of engagement and the development of social skills such as collaboration are key factors in the success of PBL. However, challenges such as difficulties in understanding complex concepts and disparities in student participation also emerged. The implications of the study highlight the need for a supportive learning environment to enhance student motivation. Recommendations for teachers include providing constructive feedback and clearly defining roles within groups. Future research is suggested to involve more participants and explore external factors influencing the effectiveness of PBL. These findings affirm that PBL not only enhances academic understanding but also enriches students' overall learning experiences. KEYWORDS Keyword_1. Project-Based Learning Keyword_2. Understanding of Chemistry Concepts Keyword_3. Understanding of Chemistry Concepts